2019
DOI: 10.3389/fphys.2019.01061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolonged Head-Down Bed Rest on Cardiac and Vascular Baroreceptor Modulation and Orthostatic Tolerance in Healthy Individuals

Abstract: Orthostatic intolerance commonly occurs after prolonged bed rest, thus increasing the risk of syncope and falls. Baroreflex-mediated adjustments of heart rate and sympathetic vasomotor activity (muscle sympathetic nerve activity – MSNA) are crucial for orthostatic tolerance. We hypothesized that prolonged bed rest deconditioning alters overall baroreceptor functioning, thereby reducing orthostatic tolerance in healthy volunteers. As part of the European Space Agency Medium-term Bed Rest protocol, 10 volunteers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 57 publications
(111 reference statements)
4
31
2
Order By: Relevance
“…Previous studies showed worsened cardiopulmonary fitness and orthostatic tolerance. 8 Yet we did not observe sustained reductions in left ventricular function assessed by systolic strain analysis in line with shorter duration bed rest studies. 9 Finally, myocardial mass did not change significantly, suggesting that cardiac atrophy is not a general feature during physical deconditioning and cannot be seen as risk factor for developing chronic heart failure.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies showed worsened cardiopulmonary fitness and orthostatic tolerance. 8 Yet we did not observe sustained reductions in left ventricular function assessed by systolic strain analysis in line with shorter duration bed rest studies. 9 Finally, myocardial mass did not change significantly, suggesting that cardiac atrophy is not a general feature during physical deconditioning and cannot be seen as risk factor for developing chronic heart failure.…”
Section: Discussionsupporting
confidence: 81%
“…However, in both groups the incidence was very low, potentially due to the fact that subjects were permitted to perform isometric leg muscle pump exercises when experiencing symptoms. In the absence of countermeasures, bed rest deconditioning is associated with markedly reduced orthostatic tolerance [ 37 ]. Interestingly, we did not observe worsening tolerability of short-arm centrifugation over time suggesting that daily artificial gravity may have maintained orthostatic tolerance but this requires further evaluation including specific testing of orthostatic tolerance during bed rest [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged bedrest (there have been extensive studies of head-down bedrest simulating chronic weightlessness in astronauts) leads to reduced cardiac output and stroke volume, hypovolaemia, baroreflex impairment, and withdrawal of the sympathetic neural response. [12][13][14][15]…”
Section: 'Long Covid' and Orthostatic Intolerance Syndromesmentioning
confidence: 99%